2016
DOI: 10.21595/jve.2016.16600
|View full text |Cite
|
Sign up to set email alerts
|

Self-sensing cavitation detection capability of horn geometries for high temperature application

Abstract: Cavitation is utilized in a wide range of applications. As examples ultrasonic cleaning baths and emulsification in sonochemistry may be mentioned. For a high temperature ultrasonic assisted casting process, the authors’ aim is to detect cavitation in the ongoing process using cavitation noise spectra without additional sensors like hydrophones, which disturb the sound field. The authors’ aim is to detect cavitation from the ultrasonic transducers’ current signal. Two different horn geometries are tested for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The basis behind this method can be classified into two main domains. One is through the evaluation of indicators in the frequency domains, found in the electrical signals of the transducer [33,34] and the other is related to the evaluation of the transducer impedance [32]. However, several frequency portions, such as harmonics and the global noise level, are also part of the characteristic of the transducer; so, it is difficult to estimate the cavitation intensity through the current signal spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The basis behind this method can be classified into two main domains. One is through the evaluation of indicators in the frequency domains, found in the electrical signals of the transducer [33,34] and the other is related to the evaluation of the transducer impedance [32]. However, several frequency portions, such as harmonics and the global noise level, are also part of the characteristic of the transducer; so, it is difficult to estimate the cavitation intensity through the current signal spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In acoustic cavitation, the generated frequency components are mostly related to the driving frequency f 0 of the ultrasound transducer [3][4][5][6][7][8][9][10]. Researchers [11][12][13][14] have shown that with a so called self-sensing technique, that is using the ultrasound transducer simultaneously as both an actuator and a sensor, indicators for the presence of cavitation can be detected by observing the transducer's electrical signals. By now the transducer data [12,13] have been compared to those of microphones and hydrophones in order to reach a conclusion on the processes in the fluid.…”
Section: Introductionmentioning
confidence: 99%
“…These recent publications show that closed loop control of cavitation is a valuable target. Additional motivation to implement closed loop cavitation control are high power processes such as ultrasonic assisted hybrid casting [14], there cavitation is utilized to enable a pure metallic bond between aluminum melt and solid copper. The intensity of cavitation is crucial for the quality of the connection.…”
Section: Introductionmentioning
confidence: 99%